Challenges in multi-agency collaboration in disaster management: A Sri Lankan perspective. (August 2021) - Abdeen, F.N.; Fernando, T.; Kulatunga, U.; Hettige, S.; Ranasinghe, K.D. Arjuna
Abstract: This study was aimed at investigating the current challenges prevailing in relation to multi-agency collaboration during disaster management and at the strategies that should be implemented in order to overcome such challenges. The study was based on a qualitative approach under which 32 semi-structured interviews were carried out among agencies engaged in disaster management. The collected data were analysed using content analysis. The study identified seven challenges that hinder multi-agency collaboration (communication, environmental, social, political, inter-organisational, intra-organisational and infrastructure challenges) and corresponding strategies that can be used to overcome them. Communication was considered as the dominant challenge due to the lack of a technology platform and well-defined guidelines for sharing data among the agencies to establish a common view of the disaster context. Furthermore, the interoperability challenges that exist among the agencies seems to hinders the effective collaboration among agencies.